Adsorptive Capacity of Activated Carbon from Algarrobo as Fixed Bed for Nickel Adsorption - Contreras, Jefferson; Colina, Gilberto; López, Danilo; Campos, Williams; Rincón, Nancy (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
Adsorption column tests, using granular activated carbon CAA as fixed-bed at constant operating column parameters, were performed, including: fixed bed length, flow rate, nickel initial concentration in the influent solution, and changing the pH of the influent solution at 3.00, 4.50 and 6.00. The results showed that a pH value of 6.00, the evaluation parameters were much more successful than the rest of the pH of the solution studied. tb = 5.76 min, ts = 119 min, Vef = 170 mL, LZTM= 8.19 cm,qeq=2.36 mg í—g -1 y un RT = 88.91 % values were obtained. The Yoon-Nelson model was applied to the experimental data to describe the behavior of the breakthrough curve, found that the values were adjusted successfully to model because the linear correlation obtained, with R2 values greater than 0.96. Breakthrough curves, observed and calculated, showed the typical “S”-shape that characterizes them, with different points of inflection; reflecting more widened and steeper as the pH value in the influent solution was increasing.